Grand challenges of smart technology for older adults - Zhou, Jia; Salvendy, Gavriel; Boot, Walter R.; Charness, Neil; Czaja, Sara; Gao, Qin; Holzinger, Andreas; Ntoa, Stavroula; Rau, Pei-Luen Patrick; Rogers, Wendy A.; Stephanidis, Constantine; Wahl, Hans-Werner; et al. (International journal of human computer interaction, 2025)
Smart devices, systems, and services are transforming various aspects of daily life, offering new opportunities for the well-being of older adults. This article explores the grand challenges associated with evolving smart technology for the aged population. Based on the collective effort of 13 experts, their insights were categorized into six grand challenges of smart technology for older adults: DISUSE (underutilization of smart technology), USE (user knowledge, goal complexity, and risk-potential tradeoff), MISUSE (overreliance on smart technology), ABUSE (in appropriate application of smart technology), TIME (evolving relationship between older adults and smart technology), DOMAIN (potential and barriers of technology use in health, home, and work). Each grand challenge is further elaborated through its components or emerging issues, leading to implications for elderly-friendly smart technology. Addressing these challenges requires collaborative efforts to ensure that smart technology effectively enhances active and healthy aging.